Suicidal Moral Motives (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article presents an in-depth analysis of the psychological, social, and individual motives of suicidal behavior. It examines risk factors contributing to suicide among adolescents and young adults, along with effective prevention strategies and methods of psychological intervention. Based on research findings, practical recommendations are provided for professionals working with youth